Wear rate reduction mechanism of minimum quantity lubrication to enhance machinability using hybrid nano-coolant (TiO2- Al2O3) - Wajiha Tasnim, Urmi (2021)
In the advanced manufacturing world, the applications of aluminium alloys are dramatically increasing in various engineering fields due to their exciting mechanical properties. The machining of aluminium alloy has the challenges of occurrences of tool wear, surface degradation forming built-up edge, adhesion due to high heat and friction at the contact zone. Hence, proper cooling and lubrication technique can improve machining efficiency by minimizing tool wear, friction, surface roughness. Recently, researchers have been giving priorities to the Minimum Quantity Lubrication (MQL) technique using minimum fluid compared to conventional coolant technique. Hence, the objective of this study to investigate machining performance in terms of the tool wear mechanism, including surface roughness, material removal rate and to develop multi-objective optimization of end milling of aluminium alloy with conventional flooded and hybrid nanofluid (HNF) MQL conditions. The TiO2-Al2O3 hybrid nanofluid is synthesized for volume concentration from 0.02 to 0.1% using the two-step synthesis method. The stability of hybrid nanofluids is assessed using zeta potential test, UV- Vis spectral analysis, sedimentation photograph and the thermophysical properties are measured for the temperature range of 30 to 80 oC. For machining central composite design of response surface methodology is followed. The study considers the flow rate of commercial mineral oil (added 5 % with water) as 30 L/min for the flooded condition and the flow rate of HNF as 0.3 to 1.2 ml/min for the HNF-MQL condition. The mechanism of tool wear is presented using SEM micrographs with EDX analysis as well as the interaction of tool wear with surface roughness and material removal rate is also analysed. The study reveals that the TiO2-Al2O3 hybrid nanofluid has a stability period of more than one month, showing standard zeta potential value (more than 30 mV), absorbance ratio (more than 80 %) with no apparent sedimentation. Besides, the new HNF also shows significant improvement of thermophysical properties in terms of thermal conductivity (37.44%) and viscosity (101.22 %). In the case of machining, second-order mathematical models of tool wear, including the surface roughness and material removal rate, are developed for both cooling conditions with excellent accuracy. Adhesion, abrasion marks, built-up edge, edge breakage or chipping are the significant wear of the study for both conditions. The performance of HNF-MQL machining in terms of considered response factors shows significant improvement compared to flood machining. Among all the response factors, tool wear (29 %) and surface roughness (30.13 %) noticeably improved for the application of HNF-MQL, followed by material removal rate (12.16 %). The material removal rate also shows consistency for the HNF-MQL condition. Besides, the tool wear mechanism shows a significant relationship with the efficiency of machining, revealing a significant interaction with surface roughness and material removal rate. Finally, from optimization results, tool wear is improved by 21.36 %, while the surface roughness is improved by 80.90%. Hence, experimental results revealed the prospective utilization of hybrid nanofluids in machining as coolant. Beneficial results of the study in HNF characterization terms and machining performance measures compared to flood machining suggest that researcher and engineers study and apply various types of HNF-based MQL technique in advanced manufacturing industries.